Pengembangan Agrowisata Berbasis Komunitas Melalui Program Edukasi Wisata dan Entrepreneurship Menuju Kemandirian Ekonomi Masyarakat - Ahmad Badrut Tamam; Siti Fahimah (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2020)
The agriculture-focused tourisme, then called agro-tourism has been applied in some areas, but each region has different land character. Besur, one of the villages in Lamongan, has WBAE as one of the agrotourisme with its own specification, namely suitable for rice and the like. The WBAE grows very fast by the hard commitmens and spirit of the managers but they should do the total quality improvement to stand for its existence. The accompaniment is aimed to keep and make the continuous quality improvement then equl with the other agro-tourism. The approach used is ABCD (Asset Based Community Development) it’s implemented by maximizing the assets owned by the village it passes three steps, such as deram, design, define and destiny. It’s applied by improving the quality of the WBAE assigmnet implementation team TPK in place management and enhanting the intrepreneurial quality of human resources. The programs have been applied including the tourism management training to improve the human resources of TPK WBAE, the setting of WBAE TPK jobs list and WBAE development design as well.